PENGEMBANGAN PEMBELAJARAN MATEMATIKA HUMANISTIK UNTUK MENINGKATKAN KEMAHIRAN MATEMATIS (Unnes Journal of Mathematics Education Research, 2012)
AbstrakPenelitian ini mengkaji pengembangan dan pengimplementasian perangkat pembe-lajaran matematika humanistik untuk SMP. Model pengembangan yang digunakan adalah model pengembangan Van den Akker dan Plomp. Perangkat yang dikem-bangkan (1) silabus, (2) RPP, (3) buku siswa, (4) Lembar ktivitas siswa, dan (5) tes kemahiran matematis. Hasil penelitian diperoleh hasil pengembangan perangkat pembelajaran matematika humanistik untuk SMP yang valid dan implementasinya efektif.AbstractThis study aims to assess the development and implementation of  humanist mathematics learning instrument for junior high school.  The development model used  is  development model of  Van den Akker and Plomp. The developed learning intrument are:  (1) syllabus, (2) lesson plan, (3) student book, (4) work sheet of  student activity, and (5) mathematical skill test. The results of  this study indicate that development of  humanist mathematics learning instrument for junior high school is valid, practical, and its implementation is effective.